Rent-sharing : Does the Bargaining Regime Make a Difference? Theory and Empirical Evidence - Nicole Gürtzgen (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
This paper analyses whether wages in Germany respond to firm-specific profitability conditions. Particular emphasis lies on the question of whether the extent of rent-sharing varies across different systems of wage determination. Those may be categorised into sector-specific wage agreements, firm-specific wage agreements and wage determination without any bargaining coverage. To derive testable hypotheses, we set up a theoretical model that analyses the sensitivity of wages to firm-specific conditions under different wage setting structures. The hypotheses are tested using an establishment-level panel data set from the mining and manufacturing sector. The results of the empirical analysis generally suggest that rent-sharing is present in Germany. However, the extent of rent-sharing is found to be significantly lower in establishments that are subject to a collective wage agreement - irrespective of whether the agreement is industry- or firm-specific. While pooled OLS estimates yield positive estimates of the rent-sharing coefficient in establishments that are covered by a collective contract, SYS-GMM-estimates accounting for unobserved heterogeneity and endogeneity of rents point to a rent-sharing coefficient of zero.
Keywords: J31; C23; J51; 330; Rent-Sharing; Wage-Setting Structure; Unions; Panel Data; Lohnbildung; Lohnverhandlungstheorie; Rententheorie; Niederlande